2007
DOI: 10.1111/j.1365-2524.2007.00691.x
|View full text |Cite
|
Sign up to set email alerts
|

Listening to people with intellectual disabilities who misuse alcohol and drugs

Abstract: There is a dearth of research that has explored alcohol/drug use and misuse by people with intellectual disabilities. The aims of the present study were twofold: (1) to examine the insights of 10 people with intellectual disabilities into the reasons why they may misuse alcohol or drugs, and what impact this behaviour may have on them; and (2) to explore the services that they receive. Ten individuals with intellectual disabilities who were deemed to be misusing alcohol/drugs were purposively selected and inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 20 publications
1
51
0
5
Order By: Relevance
“…A study of life histories [35] suggested that the development of a self-injury/self-harm conundrum in individuals with severe intellectual disabilities might be a response to traumatic life experiences. In this same line, and also through case studies, Taggart et al [36] found that the less frequent phenomenon of misuse of alcohol and drugs in PWID may also be a consequence of 'psychological trauma' and 'distance from the community'. Multiple deaths of close family members, death of partners, long-term physical, emotional and financial abuse, sexual abuse or rape were also identified in the case studies.…”
Section: Murphy Et Al [33mentioning
confidence: 89%
“…A study of life histories [35] suggested that the development of a self-injury/self-harm conundrum in individuals with severe intellectual disabilities might be a response to traumatic life experiences. In this same line, and also through case studies, Taggart et al [36] found that the less frequent phenomenon of misuse of alcohol and drugs in PWID may also be a consequence of 'psychological trauma' and 'distance from the community'. Multiple deaths of close family members, death of partners, long-term physical, emotional and financial abuse, sexual abuse or rape were also identified in the case studies.…”
Section: Murphy Et Al [33mentioning
confidence: 89%
“…The changes that occur when the individual with disabilities uses psychoactive substances were described in study as physiological effects, the effects upon the person's mind and the financial implications, damage in the relationships with their families, partners and peers, often resulting in verbal and physical confrontations when drinking [19].…”
Section: Discussionmentioning
confidence: 99%
“…A study with people with visual impairments identified that the reasons to drink are related to leisure and entertainment, especially among young adult men [24]. The use of psychoactive substances may also be related to psychological trauma as deaths of family members; lack of company and friends; loneliness; isolation; exploitation of partners; sadness; confusion [16]. It is noteworthy also the use of substances to control the symptoms of mental illness and minimize the side effects of medications [18].…”
Section: Substance Uses By People With Disabilitiesmentioning
confidence: 99%
“…As a result of substance use, one of the reviewed studies reported psychological effects, effects on the mind, financial implications, verbal and physical confrontation, amnesia, suicidal ideation, loss of independence, discussions with family, violent behavior [16].…”
Section: Substance Uses By People With Disabilitiesmentioning
confidence: 99%
See 1 more Smart Citation